Pendampingan Pencatatan Laporan Keuangan Pada UMKM - Pinem, Anwar Arifin; Siti Rahmayuni; Ekki Satria Jaya; Eko Edy Susanto (BADAN PENERBIT STIEPARI PRESS, 2023)
Balikpapan is a supporting city for the Capital of the Archipelago, which must have a notable icon for its progress. It comprises six districts, one of which is Balikpapan Tengah, consisting of six sub-districts: Gunung Sari Ilir, Gunung Sari Ulu, Mekar Sari, Karang Rejo, Sumber Rejo, and Karang Jati. The area is home to 4,575 Micro, Small, and Medium Enterprises (MSME). The objective of financial report recording assistance is to aid MSME in calculating the costs incurred in producing goods or products intended for sale by business operators.The assistance method involves providing training and guidance for entrepreneurs who join the MSME forum in each sub-district. The outcome of this assistance is that business operators can calculate production costs, determine the selling price, and create financial reports, including cash flow and profit and loss statements. This initiative aims to elevate Balikpapan's status by empowering MSME in Balikpapan Tengah to better manage their financial aspects. By enabling entrepreneurs to accurately calculate production costs and set competitive prices, the program contributes to the economic development and sustainability of these businesses. The training and guidance provided through the MSME forum serve as a crucial step towards enhancing the overall economic landscape of Balikpapan